2015
DOI: 10.1080/00063657.2015.1058745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extreme weather events on breeding parameters of the White StorkCiconia ciconia

Abstract: Summary 12Although the White Stork avoids adverse weather conditions modifying its arrival and 13 breeding, it cannot avoid extreme weather events during the breeding season. 14 Aims 15To show how extreme weather conditions can influence breeding attempts of a large, long-16 lived species, the White Stork. 20We analysed breeding success and breeding failure rate from 1974 -2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 55 publications
(72 reference statements)
1
26
1
Order By: Relevance
“…The general dietary composition of the studied white storks was similar to that determined in field conditions: mammals were taken in great numbers, followed by birds and fish (Pinowska and Pinowski 1989; Pinowski et al 1991; Antczak et al 2002; Kosicki 2010, 2012; Chenchouni et al 2015; Tobółka et al 2015; Chenchouni 2016). Amphibians, traditionally considered common prey for the white stork, contribute to its diet to a variable degree depending mainly on weather conditions (Schierer 1967; Pikulik et al 2001; Antczak et al 2002; Profus 2006; Kosicki et al 2006) but in experimental conditions were eaten rather rarely.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The general dietary composition of the studied white storks was similar to that determined in field conditions: mammals were taken in great numbers, followed by birds and fish (Pinowska and Pinowski 1989; Pinowski et al 1991; Antczak et al 2002; Kosicki 2010, 2012; Chenchouni et al 2015; Tobółka et al 2015; Chenchouni 2016). Amphibians, traditionally considered common prey for the white stork, contribute to its diet to a variable degree depending mainly on weather conditions (Schierer 1967; Pikulik et al 2001; Antczak et al 2002; Profus 2006; Kosicki et al 2006) but in experimental conditions were eaten rather rarely.…”
Section: Discussionsupporting
confidence: 58%
“…The experiment was carried out during the breeding season (May, June). At this time, the behaviour and physiology of white stork females in the wild is linked with production and incubation of relatively large eggs, brood care that results in spending much more time in the nest than males, whereas the latter mainly defend territories and deliver food to their nests (Collopy 1984; Hawkins 1986; Sasvári and Hegyi 2001; Deeming 2002b; Bocheński and Jerzak 2006; Kosicki 2010, 2012; Tobółka et al 2015; Żołnierewicz et al 2016). Thus, it is possible that the preferences of female white storks for avian prey might be an indication for fast supplementation of calcium and other nutrients which are more readily available from avian skeletons than from mammalian (Bilby and Widdowson 1971; Graveland and van Gijzen 1994; Poulini and Brigham 2001; Reynolds et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The white stork is mostly a solitary breeder in western Poland, but small aggregations of up to five pairs are also observed, mainly in small river valleys. The population density ranged from 5.24 to 6.76 pairs/100 km 2 (Tobolka et al 2013(Tobolka et al , 2015(Tobolka et al , 2018.…”
Section: Study Areamentioning
confidence: 99%
“…When necessary, we conducted additional visits, mainly to late broods, when the chicks were too small in July for us to assume their ability to fly. We supplemented all uncertain records by interviews with householders living near the nest; if they did not clarify the breeding status of the nest, we excluded the brood from further analyses (Tobolka et al 2015). As occupied nests (1), we coded nests built in previous years and newly built nests with a breeding pair (based on criteria proposed by Profus (2006)).…”
Section: Data Collectionmentioning
confidence: 99%
“…It has also been suggested that climate change not only means higher temperatures but also more frequent extreme weather events (Tebaldi et al 2007; Coumou and Rahmstorf 2012; McCarthy et al 2012; Zhang et al 2012; Tang et al 2013; Richter 2015; Feser et al 2015). Extreme weather events are likely to disturb life history strategies of some species and make it more difficult for organisms to adapt to local environments (Visser 2008; Chamberlain and Pearce-Higgins 2013; Tobolka et al 2015; Indykiewicz 2015). On the other hand, it was suggested that the recent extreme weather events can be treated as a natural experiment that may elucidate the mechanisms by which birds adjust their phenology to fluctuating environments (Wesołowski et al 2016).…”
Section: Introductionmentioning
confidence: 99%